The Influence Of Financial Stressors, Financial Behavior, Risk Tolerance, Financial Solvency, And Financial Knowledge On Financial Satisfaction Of Working Age Population - Anisah Firli; Shafira Khairunnisa; Dadan Rahadian (Jurnal Manajemen Indonesia, 2021)
Financial satisfaction is the ultimate goal of individuals who work hard and manage their finance. Working-age is the time when individuals are considered able to work and earn, yet they tend to fail to meet the expected financial satisfaction due to several factors. This research aims to test the influence of financial stressors, financial behavior, risk tolerance, financial solvency, financial knowledge on financial satisfaction. This research includes all important variables (financial stressors, risk tolerance, and financial solvency) that can determine financial satisfaction. The participants in this research were 100 respondents, selected by convenience sampling, from the working-age population in Jakarta, the capital city of Indonesia, who gave the biggest contribution to the economy. The data were analyzed by using multiple linear regression analysis. The findings show that financial stressors, financial behavior, risk tolerance, financial solvency, and financial knowledge simultaneously had a significant influence on financial satisfaction. Partially, only risk tolerance and financial knowledge variables affect financial satisfaction. The findings imply that the working-age population should manage financial stressors, financial behavior, risk tolerance, financial solvency, and financial knowledge properly to improve financial satisfaction reflecting financial welfare.